Comparative Research of Motivations across Different Festival products - Yolal, M.; Woo, E.; Cetinel, F.; Uysal, Muzaffer (Emerald Group Publishing Limited, 2012)
Purpose – The study has three objectives. The first objective of this paper is to investigate the underlying dimensions of motivation for attending an international festival in Turkey and whether motivation will vary across six different festival products (symphony, rock, world music, dance, ballet, and theater). The second purpose is to understand how festival attendees perceive the socio‐economic impacts of the festival and how these perceived impacts vary across different festival attendee groups. Finally, the study examines the overall satisfaction of festival attendees with respect to different festival products. Design/methodology/approach – The empirical data was collected by way of self‐administered questionnaires to obtain perceptions and motivations of 523 attendees in Eskisehir International Festival. Findings – The results showed that there were significant differences in motivation among attendees from six different festival products. Duncan's multiple‐range tests were performed to further examine differences in motivation among these attendees. The mean scores of different groups indicate that “rock event” attendees tended to have lower motivation scores than other groups and have the lowest ratings on the factor of “family togetherness”. However, attendees did not differ on the perceived importance of socio‐economic impacts and satisfaction with the festival, irrespective of the festival product attended. Originality/value – Festivals and special events have increased worldwide because they provide significant economic, socio‐cultural, and political impacts on destinations. While a plethora of studies have examined tourists' motivation and socio‐economic impacts, little research has been conducted on the motivation and socio‐economic impact of festival attendees with regard to different product offerings.